Argument-based decision making in ambient intelligence environments - Marreiros, Goreti (2009)
Decision making is a cognitive process of the foremost importance to set a line of action under change; it is said to be a psychological construct, being therefore latent and not directly observable. Indeed, issues of construct validity are paramount, where the information gathered would provide insight regarding the construct of emotional intelligence and how one would attempt to clarify its meaning and measure it. In this paper, this problem will be addressed in terms of an argumentation-based system, where intelligent agents simulate the behaviour of individuals as group members that take part in a decision making process.